Figuring Out Commercial Gimmicks Influencing Consumer Engagement from Psychological Change Points - Seguchi, Motoki (Advances in Social Sciences Research Journal, 2022)
Although the scale is not so large, there are many companies that carefully manufacture traditional products of high quality such as crafts and foods. For such companies, story-telling commercials explaining their elaborate products on their SNS sites are attractive means to enlarge their business scale, because it takes a lower cost than TV commercials. However, because of limited budgets, they make commercials for themselves. It is difficult for them to evaluate whether their commercials have an impact on consumers. To compose hand-made commercials appealing to new customers, this study proposes a method to estimate which gimmicks in a commercial affect consumer engagement. Customer targeting is important in business for the small amount of production. The study evaluates the method, dividing target consumers into two groups, students and working adults. The change point detection is applied to pupil size for estimating gimmicks affecting emotional engagement, so is to EDA for estimating ones affecting cognitive engagement. The impacts on behavioral engagement are evaluated with a questionnaire. Experiments show that characters are an important gimmick for cognitive engagement. A climax should be placed firmly in the story to influence emotional engagement. Flashback scenes also turn out useful gimmicks for both cognitive and emotional engagement. Furthermore, scenes that allow consumers to imagine themselves using the product are influential to behavioral engagement. Specific elements working well for each gimmick turn out to vary with students and adults. The method manifests gimmicks to be included in a commercial when companies compose their commercials for themselves.